Analisis Organisasi Kurikulum dan Struktur Kurikulum Anak Usia Kelas Awal Sekolah Dasar (SD)/Madrasah Ibtidaiyah (MI) - Utomo, Sandi Aji Wahyu; Azizah, Wida Nurul (Jurnal Pancar, 2018)
Analysis of the curriculum organization is closely related to the content standards of the educational curriculum which contains subject matter that will later be taught to students at school. The curriculum organization consists of certain subjects that aim to convey the culture / number of knowledge, attitudes and skills that must be taught to students. Each curriculum organization has its own advantages and disadvantages, both theoretical and practical. There are various types of curriculum organizing, which cover how the form of the field of study must be presented in front of the class which will be followed by how to choose teaching materials and how to present, evaluate them. Broadly speaking, there are three curriculum organizations, namely: Separated Subject Curriculum, Correlated Curriculum, and Integrated Curriculum